De autor a personagem: Jorge Luis Borges na mira de romancistas latino-americanos - Milreu, Isis [UNESP] (2014)
Jorge Luis Borges is regarded as one of the most important XX century writers from many critics’ and writers’ standpoint. Therefore, his poetry, which became a paradigmatic one, has revolutionized the literary practice as well as the literary studies. Currently, we observe that the Argentinian writer is not only analyzed in several essays, theses and biographies, but also the writer himself has been converted into a recurring character in various novels, short stories, chronicles, plays, films and comics. In this sense, Pablo Brescia (2008) points out that there is a tendency in fictionalizing Borges, that is, to make him into a literary object. Brescia adds that instudies on Borges there is still an ignored aspect concerning the way some writers have (re)read the Argentinian author, especially within the fictional sphere. Considering the existence of that gap we may justify the accomplishment of a study about this topic. Thus, this research work aims at contributing to the understanding of the process of Borges’ conversion into a character in the production by other writers, specifically within the scope of Latin American literature, such as, the Argentinian and Brazilian ones. Thereby, the corpus of this research consists of the following novels: Jorge Manzur’s El simulador (1990); María Rosa Lojo’s Las libres del Sur. Una novela sobre Victoria Ocampo (2004); Francisco Cappellotti’s Matar a Borges (2012); Luis FernadoVeríssimo’s Borges e os orangotangos eternos (2000); Hamilton Alves’s O romance de Borges (2000); and Antonio Fernando Borges’s Memorial de Buenos Aires (2006). We observe that those narratives are structured around Borges’ biografemas and his literature which dialogs with both Borges’ poetry and the history of literature, besides utilizing intertextuality and metafiction as main stylistic features